Hybrid hydrogels based on RAFT mediated poly(N-vinyl pyrrolidone) - Eksteen, Zaskia-Hillet (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.